Comparative evaluation of protective immunity against Francisella tularensis induced by subunit or adenovirus-vectored vaccines - Zhao, Mengsu; Zhai, Yanfang; Zai, Xiaodong; Mao, Yunyun; Hu, Enbo; Wei, Zhaodong; Li, Yan; Li, Kai; Liu, Yanhong; Xu, Junjie; Yu, Rui; Chen, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
Tularemia is a highly contagious disease caused by infection with Francisella tularensis (Ft), a pathogenic intracellular gram-negative bacterium that infects a wide range of animals and causes severe disease and death in people, making it a public health concern. Vaccines are the most effective way to prevent tularemia. However, there are no Food and Drug Administration (FDA)-approved Ft vaccines thus far due to safety concerns. Herein, three membrane proteins of Ft, Tul4, OmpA, and FopA, and a molecular chaperone, DnaK, were identified as potential protective antigens using a multifactor protective antigen platform. Moreover, the recombinant DnaK, FopA, and Tul4 protein vaccines elicited a high level of IgG antibodies but did not protect against challenge. In contrast, protective immunity was elicited by a replication-defective human type 5 adenovirus (Ad5) encoding the Tul4, OmpA, FopA, and DnaK proteins (Ad5-Tul4, Ad5-OmpA, Ad5-FopA, and Ad5-DnaK) after a single immunization, and all Ad5-based vaccines stimulated a Th1-biased immune response. Moreover, intramuscular and intranasal vaccination with Ad5-Tul4 using the prime-boost strategy effectively eliminated Ft lung, spleen and liver colonization and provided nearly 80% protection against intranasal challenge with the Ft live vaccine strain (LVS). Only intramuscular, not intranasal vaccination, with Ad5-Tul4 protected mice from intraperitoneal challenge. This study provides a comprehensive comparison of protective immunity against Ft provided by subunit or adenovirus-vectored vaccines and suggests that mucosal vaccination with Ad5-Tul4 may yield desirable protective efficacy against mucosal infection, while intramuscular vaccination offers greater overall protection against intraperitoneal tularemia.